ARTISAN CHEESE AGROINDUSTRY - Pasquini, Paulo Roberto; Ferrarezi Junior, Edemar (Revista Interface Tecnológica, 2022)
The development of the project consists in the creation of a manual capable of guiding milk producers, who wish to open an artisanal cheese factory, develop guidelines that help and direct the small milk producer and especially companies from family origins, which have few cows and its production is tiny and incapable of generating foreign exchange in its original form, thus ensuring the use of the main product produced on its properties, adding value to this product, guaranteeing a second income capable of defraying the families keeping them in the countryside to the detriment of production. of food to subsidize many other families that depend daily on the supply of this increasingly scarce food to survive.